2019
DOI: 10.4236/ce.2019.103043
|View full text |Cite
|
Sign up to set email alerts
|

Development and Usability Assessment of a Mobile Application for Neuroanatomy Teaching: A Case Study in Brazil

Abstract: The teaching of Neuroanatomy presents relevant challenges, such as, restrictions to obtain properly preserved corpses, high cost for anatomy laboratory maintenance, and difficult contextualization. This article describes the development of a mobile application using cumulative tests (retrieval-based learning approach) for neuroanatomy teaching. A case study of usability assessment was conducted with thirty undergraduate Healthy Sciences students. The application received a positive evaluation, based on the Sys… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
1
0
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(3 citation statements)
references
References 23 publications
0
1
0
1
Order By: Relevance
“…SUS) to assess the usability of a mobile application for guiding health professionals. To measure usability ratings of a mobile application for neuroanatomy, Ponte et al (2019) used two types of questionnaires: SUS to determine usability and learnability; and another five questions to determine participants' perceptions of the usefulness of the application, perceived usefulness. On the other hand, Weichbroth (2019) proposes a mixed methodology for measuring and evaluating the usability of mobile applications.…”
Section: Mixing Approaches To Measuring Usability Of Mobile Applicationsmentioning
confidence: 99%
“…SUS) to assess the usability of a mobile application for guiding health professionals. To measure usability ratings of a mobile application for neuroanatomy, Ponte et al (2019) used two types of questionnaires: SUS to determine usability and learnability; and another five questions to determine participants' perceptions of the usefulness of the application, perceived usefulness. On the other hand, Weichbroth (2019) proposes a mixed methodology for measuring and evaluating the usability of mobile applications.…”
Section: Mixing Approaches To Measuring Usability Of Mobile Applicationsmentioning
confidence: 99%
“…For the application of mobile APP in classroom teaching, there are many research results at home and abroad. For example, Ponte, a foreign education scholar, discussed how to use mobile instant messaging tools (WhatsApp) to support the teaching of higher education courses, and the results showed that students expressed positive views and acceptance attitudes towards the mobile application of WhatsApp [5]. Unfortunately, the application research of this mobile APP in other academic environments has not been in-depth.…”
Section: Related Research At Home and Abroadmentioning
confidence: 99%
“…Com essa tecnologia móvel, os estudantes e profissionais da saúde podem utilizar de modo prático livros armazenados em seus dispositivos para consultas rápidas, atualizarem-se com artigos científicos recém-publicados com maior facilidade, manusear calculadoras de aplicabilidade para a clínica médica e desenvolver aplicativos personalizados para facilitar o processo de educação médica (SHORT et al, 2014;HEEYONG et al, 2014;PEREIRA et al, 2019;PONTE et al, 2019). Mais de 92% dos profissionais do meio médico utilizam smartphones ou tablets.…”
Section: Introductionunclassified